2015
DOI: 10.1080/10942912.2015.1004587
|View full text |Cite
|
Sign up to set email alerts
|

In VitroDissolution of Calcium Carbonate from the Chicken Eggshell: A Study of Calcium Bioavailability

Abstract: In vitro dissolution is a major indicator of potential in vivo calcium absorption. It can be used to assess the bioavailability of Ca from different sources. The aim of this study was to analyze the in vitro dissolution of calcium carbonate from the eggshell samples collected before and after the incubation period. The samples of chicken eggshell were characterized by good dissolution, better than that of precipitated CaCO 3 . The dissolution of the eggshell before incubation was found to be faster than that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
2
11
0
2
Order By: Relevance
“…The result showed that Ca utilization from eggshell flour was higher compared to limestone. This result was supported by statement of Scheideler (1998) in which digestibility of eggshell flour was higher than limestone and Szeleszczuk et al (2015) stated that bioavailability Ca of eggshell was high. Leeson dan Summers (2005) stated that calcium of diet was storage in bone, deposited in eggs and excreted on the excreta.…”
Section: Ca Of Yolksupporting
confidence: 79%
See 1 more Smart Citation
“…The result showed that Ca utilization from eggshell flour was higher compared to limestone. This result was supported by statement of Scheideler (1998) in which digestibility of eggshell flour was higher than limestone and Szeleszczuk et al (2015) stated that bioavailability Ca of eggshell was high. Leeson dan Summers (2005) stated that calcium of diet was storage in bone, deposited in eggs and excreted on the excreta.…”
Section: Ca Of Yolksupporting
confidence: 79%
“…According to Dolinska et al (2016), calcium carbonat (CaCO 3 ) of eggshell has a higher solubility than of synthetic CaCO 3 . Szeleszczuk et al (2015) stated that the in vitro solubility Ca of eggshell is higher than CaCO 3 . The aim of this research was to evaluate a substitution of limestone with eggshell flour on the Ca deposition in egg of laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have proven that, during the embryonic development of the chicken inside the egg, elution and subsequent absorption of some elements from the shell occur (Szeleszczuk et al, 2015). We have also confirmed that the mechanism of calcium release from insoluble calcium carbonate is based on the formation of calcium bicarbonate Ca(HCO 3 ) 2 , (Pisklak et al, 2012) The released calcium is then used by the growing chicken embryo for the development of its skeletal system.…”
Section: Introductionsupporting
confidence: 51%
“…It is often assumed that the calcium carbonate is poorly absorbed by the body because of its insolubility. Maybe calcium citrate or calcium lactate soluble in water (in such a form it is present in milk) is better absorbed (Szeleszczuk et al, 2015). Calcium solubility in vitro study (Bradauskienė et al, 2016) demonstrated that calcium carbonate from eggshell is readily soluble in gastric juice comparing to solubility of other commercial calcium supplements such as Calcigran®, Calcivit® Coral Calcium®.…”
Section: Introductionmentioning
confidence: 99%